Sensitivity of summer stream temperatures to climate variability in the Pacific Northwest. Issue 4 (25th April 2014) - Luce, Charles; Staab, Brian; Kramer, Marc; Wenger, Seth; Isaak, Dan; McConnell, Callie
Abstract Estimating the thermal response of streams to a warming climate is important for prioritizing native fish conservation efforts. While there are plentiful estimates of air temperature responses to climate change, the sensitivity of streams, particularly small headwater streams, to warming temperatures is less well understood. A substantial body of literature correlates subannual scale temperature variations in air and stream temperatures driven by annual cycles in solar angle; however, these may be a low‐precision proxy for climate change driven changes in the stream energy balance. We analyzed summer stream temperature records from forested streams in the Pacific Northwest for interannual correlations to air temperature and standardized annual streamflow departures. A significant pattern emerged where cold streams always had lower sensitivities to air temperature variation, while warm streams could be insensitive or sensitive depending on geological or vegetation context. A pattern where cold streams are less sensitive to direct temperature increases is important for conservation planning, although substantial questions may yet remain for secondary effects related to flow or vegetation changes induced by climate change.